Protective Effect of Exclusive Breastfeeding on Acute Respiratory Infections (ARI) among Children in Tabanan, Bali - Wibawa, Putu Gede Suda Satriya; Indrarto, Fx Wikan; Samodra, Yoseph Leonardo (JHE (Journal of Health Education), 2019)
Background: ARI is one of the most causes child mortality in Indonesia due to their immature defense systems compared to adults. Intake of a toddler can affect the level of immunity against diseases, one of which is ARI. The aim of this study is to find out the correlation between exclusive breast feeding with the Incidence of Acute Respiration Infection in children.Methods: This study was performed by observational analysis experimental design with crosssectional method. The number of sample in this study was 70 children and the sample took from children that visit Puskesmas Tabanan III. Data were collected by Musfardi Rustam's (2010) questionnaire.Results: Statistical bivariate analysis by the chi-square test show a correlation between exclusivebreastfeeding with the Incidence of Acute Respiration Infection in children (p<0,01). There were no correlations between age of the children (p = 0,567), mother's education level (p = 0,601), and children’s gender (p = 0,161) with the Incidence of Acute Respiration Infection in children. Statistical bivariate analysis by Spearman rank show There were no correlations between low birth weight with the Incidence of Acute Respiration Infection in children.Conclusion: There is a correlation that clinically and statistically significant between exclusive breastfeeding with the Incidence of Acute Respiration Infection in children. There were no correlations between the age of the children, mother's education level, children’s gender and low birth weight with the Incidence of Acute Respiration Infection in children.